QUR’ANIC PARENTING: DEMOCRACY AND PARENTAL ROLE MODELING IN THE TAFSĪR AL-TAḤRĪR WA AL-TANWĪR BY MUHAMMAD AL-TAHIR IBN ASHUR - Said Baehaki; Eka Prasetiawati; M. Agus Mushodiq (Program Pascasarjana UIN Sumatera Utara, 2026)
Parental mistakes in child-rearing often trigger developmental crises in children, making Qur’anic parenting a solution-oriented paradigm that integrates dialogic interaction, discussion communication, and exemplary behavior (uswah). This qualitative study explores parenting principles through Diana Baumrind’s theories of authoritarian, authoritative, and permissive parenting in the exegesis Al-Taḥrīr wa al-Tanwīr by Muḥammad al-Ṭāhir Ibn ‘Āshūr, with a thematic analysis focusing on verses regarding parent-child interaction in Surah Hūd [11]:42–43, Yusuf [12]:4–5, Maryam [19]:42–43, As-Saffat [37]:102, and Luqman [31]:17–19. The methodology combines the approaches of Mustofa Muslim and maqāṣidi sharia to unravel adaptive parenting patterns of democratic dialogue (Nuh, Yusuf, Ibrahim with his father) that build independence, exemplary behavior (Luqman), and the internalization of moral values. This study fills a crucial gap in thematic exegesis by formulating the first authoritative-permissive and authoritarian-permissive frameworks of Qur’anic parenting based on Ibn ‘Āshūr’s previously unexplored novelty. Key contributions include: (1) a synthesis of maqāṣidi for contemporary parenting, (2) empirical validation of the democracy-exemplarity model through thematic analysis, and (3) practical guidelines for parents, enriching the discourse on Islamic psychology and family education. Thus, this study not only strengthens the theoretical foundation of the Qur’an as a source of transformative parenting but also motivates compassionate parenting practices to foster a generation resilient in spiritual and moral terms.